A Development Focus: Implication for Counsellor Education - Paisley, Pamela O.; Benshoff, James M. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article provides a rationale for the use of cognitive developmental theory as a framework for counsellor education, discusses the implications for preparation programs, and suggests evaluation and research possibilities in this area.